Robotic-assisted lobectomy for locally advanced N2 non-small cell lung cancer - Lin, Jules (Journal of Thoracic Disease, 2019)
In their surgical technique article, “Three-arm robot-assisted thoracoscopic surgery for locally advanced N2 non-small cell lung cancer”, Cheng et al. describe their approach to robotic lobectomy (RATS) in a patient with a clinical T1N2M0 adenocarcinoma (1). They underscore several advantages of a robotic approach and provide an excellent illustrative video. Minimally invasive approaches to pulmonary resection, including robotic approaches, are generally preferred due to decreased morbidity, length of stay (LOS), and quicker recovery. While initially there were concerns regarding oncologic outcomes, several studies have reported equivalent outcomes to open lobectomy with decreased chest tube duration, pain, postoperative complications, and LOS (2-4). However, the use of minimally-invasive approaches for locally-advanced disease, especially after induction therapy, is more controversial and the data more limited.